1998
DOI: 10.1083/jcb.141.7.1589
|View full text |Cite
|
Sign up to set email alerts
|

Structural Analysis of Drosophila Merlin Reveals Functional Domains Important for Growth Control and Subcellular Localization

Abstract: Merlin, the product of the Neurofibromatosis type 2 (NF2) tumor-suppressor gene, is a member of the protein 4.1 superfamily that is most closely related to ezrin, radixin, and moesin (ERM). NF2 is a dominantly inherited disease characterized by the formation of bilateral acoustic schwannomas and other benign tumors associated with the central nervous system. To understand its cellular functions, we are studying a Merlin homologue in Drosophila. As is the case for NF2 tumors, Drosophila cells lacking Merlin fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
153
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(170 citation statements)
references
References 37 publications
16
153
1
Order By: Relevance
“…The accumulation of Merlin at cell-to-cell junctions in confluent epithelial and endothelial cells [5,7], within lamellipodia in various types of cell [62][63][64], and on the surface of endocytic vesicles in Drosophila epithelial tissues [53,65] is consistent with this general hypothesis (Sidebar C).…”
Section: Merlin Localizationsupporting
confidence: 65%
“…The accumulation of Merlin at cell-to-cell junctions in confluent epithelial and endothelial cells [5,7], within lamellipodia in various types of cell [62][63][64], and on the surface of endocytic vesicles in Drosophila epithelial tissues [53,65] is consistent with this general hypothesis (Sidebar C).…”
Section: Merlin Localizationsupporting
confidence: 65%
“…It is worth mentioning that the methione residue at position 177 in the Blue Box is conserved among all merlin proteins, but not in the ERM proteins. These results further corroborate the functional importance of these amino acids in the Blue Box [46].…”
Section: Construction Of a Phylogenetic Tree For The Ermfamily Ofprotsupporting
confidence: 80%
“…In addition, the human NF2 gene could rescue the lethal merlin mutant allele in Drosophila, implying a functional conservation (LaJeunesse et al, 1998).…”
Section: Security Classificationmentioning
confidence: 97%
“…It is widely held that tumor-suppressor mutants often act in a dominant-negative fashion to promote tumorigenesis (Nigro et al, 1989). Various merlin deletion mutants have been shown to promote tumorigenesis (Koga et al, 1998;Lajeunesse et al, 1998;Giovannini et al, 2000), but whether their effects are the result of a dominantnegative or a gain-of-function prooncogenic activity has not been resolved. Tr6BC1 cells express merlin endogenously (Figure 1a), and the results of RT-PCR together with DNA sequencing indicated that both merlin isoforms I and II are expressed (data not shown).…”
Section: Discussionmentioning
confidence: 99%